2013
DOI: 10.1159/000348588
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Cognitive Therapy for Patients with Medically Unexplained Symptoms: A Randomized Controlled Trial

Abstract: Background: Patients with medically unexplained symptoms make heavy demands on the health care system. An offer for psychological treatment is often declined. There is a need for acceptable and effective treatments. We assessed the acceptability and effectiveness of mindfulness-based cognitive therapy (MBCT) for patients with persistent medically unexplained symptoms. Method: A randomized controlled trial comparing MBCT (n = 64) to enhanced usual care (EUC; n = 61). Participants were the 10% most frequently at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 85 publications
(47 reference statements)
2
39
1
1
Order By: Relevance
“…This finding is in line with the treatment goal of our MBCT program and psychotherapeutic interventions of CP in general, which is not to remove or reduce the pain itself, but rather to find ways of managing the pain and the adverse consequences on mental health and quality of life. Interestingly, a recent randomized controlled trial from van Ravesteijn et al (2013) focusing on MBCT for patients with medically unexplained symptoms, including CP, also found significant improvement on mental health functioning, in particular with regard to vitality, but no significant findings on physical health and bodily pain.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the treatment goal of our MBCT program and psychotherapeutic interventions of CP in general, which is not to remove or reduce the pain itself, but rather to find ways of managing the pain and the adverse consequences on mental health and quality of life. Interestingly, a recent randomized controlled trial from van Ravesteijn et al (2013) focusing on MBCT for patients with medically unexplained symptoms, including CP, also found significant improvement on mental health functioning, in particular with regard to vitality, but no significant findings on physical health and bodily pain.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention vs AC Combined Combined Plews-Ogan et al, 37 2005 Combined C ombined C ombined Van Ravesteijn et al, 35 2013 Intervention vs AC Combined Combined de Vibe and Moum, 39 2006 Intervention vs PC Combined Posttest Mental Health Intervention: n = 295 Control: n = 234…”
Section: Findings In Contextmentioning
confidence: 99%
“…Intervention vs AC Combined Combined Plews-Ogan et al, 37 2005 Combined C ombined C ombined Van Ravesteijn et al, 35 2013 Intervention vs AC Combined Combined de Vibe and Moum, 39 observed a moderate effect size when comparing MBIs with wait list controls, but this effect was small when compared with active controls, and even smaller when including psychotherapy. The authors concluded that MBIs did not differ from cognitive behavior therapies or pharmacotherapy.…”
Section: Posttestmentioning
confidence: 99%
“…Furthermore, van Ravesteijn et al [20,21] studied the effect of MBCT on somatizers (patients with persistent unexplained physical symptoms) in a sample of primary care patients. The authors observed that although there was no difference in overall health within this sample compared to patients who followed standard treatments, mindfulness improved psychological functioning without increasing costs.…”
Section: Cost Effectiveness Of Mbismentioning
confidence: 99%